FEASIBILITY ANALYSIS OF INVESTMENT ASSETS FOR BUSINESS DEVELOPMENT IN THE CALCULATION OF CAPITAL BUDGETING IN SURABAYA UD RAHAYU - Desi Harmada Wiratama (IJESS International Journal of Education and Social Science, 2020)
This study discusses the production house purchase investment analysis and machine at Rahayu UD in Surabaya in terms of the financial aspect. The purpose of this study was to determine whether the proposed investments made Rahayu UD provides the benefits or otherwise making it feasible to run or not. The data used is primary data (interview with the parties can provide information for this study) and secondary data obtained from the study of literature. This type of research is descriptive qualitative. The analysis method used is the investment eligibility criteria consisting ofNet Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP) and Profitability Index (PI) as a method of investment appraisal of the financial aspects. The results showed PP for 1.8 years, then declared eligible for faster compared with a target return on investment. NPV is positive at 300 281 359 to be eligible for a positive outcome. PI 1,283 to be eligible for a value greater than 1. And 15.932% IRR to be eligible for more than the required rate. So the investment plan Rahayu UD declared "WORTH" is executed.